The National Question in Europe in Historical Context - Porter Roy; Teich Mikulas (Cambridge University Press, 1993)
The purpose of this book is to bring together comparative, national and interdisciplinary approaches to the history of great movements in the development of human thought and action. Acknowledgements, Introduction, The British Isles: Celt and Saxon, The Making of the French Nation, The National Question in Italy, The Roots of the National Question in Spain, Shifting Nationalism: Belgians and Flemings and Walloons, The Nation in German History, Nationalism and Nation-State in Germany, The National Identity of the Austrians, The Czachs, The National Question in Hungary, The Union of Dalmatia with Northern Croatia: A Crucial Question of the Croatian National Integration in the Nineteenth Century, The National Question in Poland in the Twentieth Century, Finland: From Napoleonic Legacy to Nordic Co-Operation, Index.